If it's not what You are looking for type in the equation solver your own equation and let us solve it.
35=-5x+2(x+4)
We move all terms to the left:
35-(-5x+2(x+4))=0
We calculate terms in parentheses: -(-5x+2(x+4)), so:We get rid of parentheses
-5x+2(x+4)
We multiply parentheses
-5x+2x+8
We add all the numbers together, and all the variables
-3x+8
Back to the equation:
-(-3x+8)
3x-8+35=0
We add all the numbers together, and all the variables
3x+27=0
We move all terms containing x to the left, all other terms to the right
3x=-27
x=-27/3
x=-9
| (4+8t)^2=0 | | 2x-2x+3x=15 | | 11w=42=4w | | 3x/45=x/15 | | 0.5(-4+6x)=0.3x+0.7(x+9) | | 3x+2-5x=8+2x | | 3+-k=9 | | -3(1+6)=14-y | | 59049=(3)(3)^n-1 | | 47=3x^2 | | 10(2x+6)=8(2x+12) | | 2x-16=2(1+4x) | | 10(2x+6)=8(4x+12) | | 10(2x+6)=8(2x+6) | | F(54)=2x+10 | | 10(2x+6)=8(4x+6) | | 14j-14j+j-j+2j=18 | | 3x(10+9x−x^2)=0 | | 2x-2+3x-7+x+3=23 | | 5(x-1)=28-6x | | 6x-4=2(4x-4) | | 0.7x0.6=0.2x-0.42 | | 9p+4p+5p-14p=4 | | 30x+27x^2−3x^3=0 | | 6x3=3x6= | | 10(2x+6)=8(x+10) | | 10(2x+6)=8(x+8) | | 2(6x-1)+(2x+5)=90 | | -8=7x+3x-8 | | 10(2x+6)=8(x+5) | | 10(2x+6)=8(x+4) | | 10=-14+6b |